Performance das aproximações de tempos de trânsito CRS convencional e não-convencional para o imageamento sísmico de reflexões múltiplas simétricas - ROSÁRIO, Dionis Fábio Campos do (2019)
In seismic data processing, the seismic stacking simulates zero-offset (ZO) sections from multiple coverage data. This reduces the amount of data used and increases the signal /noise ratio. In recent years, some alternative methods of seismic imaging have emerged of improve the restrictions of the conventional stacking method Common-Midpoint (CMP), and among these non-conventional methods, from the Common-Reflection-Surface (CRS) and the non-hyperbolic Common-Reflection-Surface (NH-CRS). In this study, were tested the performance of the non-hyperbolic and hyperbolic CRS traveltime approximations in synthetic seismic data to simulate zero-offset sections considering primary and symmetrical multiple reflections. We also analyzed the behavior of these approximations in the recovery of the shape and amplitude of the ZO seismic traces.